(untitled) (Strathmore Law Journal, 2022)
Governance institutions evolve within historically-marked ‘frontiers’, but the judicial sector more so, in view of its sharper normative design. The motions of courts are shown to rest upon legal principles and patterns that draw cast and moulding from inputs of scholars and jurists nurtured in the common law tradition, and their heritage has constantly attended upon the conception and formulation of the modern codified Constitution, which constantly draws upon the same for its effectuation. The Constitution, therefore, rests upon the people’s sovereign mandate, and the direct legislative signals, just as it remains predicated upon regular interpretation and re-definition by the values of the judicial order, largely evolved under the common law tradition – and thus, dependent upon the inspirational works of ages, of distinguished jurists in that tradition.